Lithium Disilicate Glass-Ceramic Surface Appearance after Acid Surface Treatment - Sana Mohammed Alrefae; Siti Sunarintyas; Widowati Widowati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2012)
Dental ceramics are widely used and studied in dentistry because they are durable, aesthetically appealing and provide excellent biocompatibility. All glass-ceramic surfaces must be etched using hydrofluoric acid (HF) to increase surface roughness determined by roughness average (Ra) before cementation to a tooth surface. This research aimed to analyze the effect of hydrofluoric acid surface treatment concentration on the surface roughness of lithium disilicate glass ceramic. A total of fifteen discs of lithium disilicate glass ceramic were prepared (10mm in diameter and 1mm in thickness). Specimens were divided into 3 groups (n=5). Group A (control) was no treatment, group B was etched by 5% HF for 2 min, and group C was etched by 9.5% HF for 2 min. The etched surfaces were observed by Scanning Electron Microscope (SEM). The measurement of the Ra of the lithium disilicate glass ceramic was determined with surface roughness tester machine. The results showed that the means of Ra (μm) were 0.096±0.009μm, 0.608±0.054μm, and 0.892±0.101μm in group A, B, and C, respectively. The one-way ANOVA showed there was an effect of hydrofluoric acid surface treatment concentration on the surface roughness of the lithium disilicate glass ceramic. The post hoc test showed there was a difference of Ra (μm) among the experimental study groups (p<0.05). In conclusion, the concentration of hydrofluoric acid influences Ra of lithium disilicate glass ceramic.